(3GdTLQI PGJ GdCceGes ((3jhSa GdeZQHi s)
(3ChdgG (B:s
(3SHMGf ef CHOY hChOY ai GdCfZGe CSQGQ NajI hCLQi Ydi bdhH ef TGA JMbjb eHGfjgG GdCUdjI hZQS CUhdgG ai acQ Phi GdCdHGH GdfhQGfjI GdHGH GdChd ai eGgjI GdehSjbi s
(3BNQgG (B:s
(3ef ETJQGc GdfZeGJ GdeJQcHI ef Pdc GdLOhd GdeJbOe HGdhUa GdeJbOe hHgG jchf JeGe gPG GdHGH aGage gPG Gdbhd hGdNWGH dJYQa GdNWC ef GdUhGH hGdMeO ddg GdYRjR GdhgGH s
(3HgG fXGe GdJYbjHIs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B6 - (3U (B7 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B8 - (3U (B255s
(3JHUQGJ GdCUd (B:s
(3MGdI GdfSNI LjOI s
(3eUOQ GbJfGA GdCUd (B:s
Keywords: (3GdehSjbi hGdZfGAs